Technical Guidance Provision in Electricity Energy Saving for Teachers and Educational Staff of SDN 09 Pontianak Timur - Putranty Widha Nugraheni; Zainal Abidin Abidin; Eka Kusumawardhani; Leonardus Sandy Ade Putra; Lalak Tarbiyatun Nasyin Maleiva (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2022)
The provision of electricity is crucial, so efficiency must be done because electrical energy is a top priority for residential, industrial, and outdoor lights. All tiers of society must support the government's efforts to ensure the stability of the nation's energy supply through initiatives to boost supply and conserve energy. The public, particularly the lower middle class, do not yet understand the existing technology well; the information of its benefits and drawbacks have not been equally spread. Energy researchers and experts assert that the domestic or household sector's contribution to the attempt to cut power usage is very significant due to the comparatively high share of residential consumers. A project must be carried out to provide counseling in the form of instruction on cost savings when utilizing electrical and electronic gadgets in homes and schools. The counseling results revealed that the teachers of SDN 09 Pontianak Timur were genuinely interested in what they were hearing and in the presented curriculum. Through the counseling technique it is observed that the community is becoming more conscious of the need to utilize electrical energy more intelligently and is gaining new insights into how to do so. These insights help the community promoting energy efficiency in daily life.